Cutaneous Amyloidosis: A Pilot Study at a Teaching Hospital in New Delhi (Journal of Medicine, 2017)
Background: Amyloidosis is characterized by the deposition of polymeric fibrillar proteins in the extracellular compartment in tissues and organs ultimately leading to damage with functional compromise. Cutaneous amyloidosis is clinically classified into more common macular, papular, and the rarer nodular form. The present study was undertaken with the aim to histopathologically analyze and characterize clinically diagnosed amyloid cases.Methods:The present study was a retrospective analysis of skin biopsies conducted over a one year period. Data on the age and presenting clinical features were retrieved from the accompanying laboratory request forms or patients records wherever available. All skin biopsies with a histologic diagnosis of amyloid were retrieved and reviewed, the pattern of amyloid deposition identified and classified. Special stains including Congo Red stain was done in all the cases.Results: Histopathological confirmation of cutaneous amyloidosis was seen in nine out of fourteen cases and was confirmed by positive Congo-red stain under polarized light. Out of this seven were females and two were males. Majority of the lesions were of macular type. In all the nine cases, family history was negative and no evidence of systemic involvement was noted, either clinically or based upon the lab investigations.Conclusions: In this pilot study of 9 cases, histologically diagnosed as cutaneous amyloidosis we noted a female preponderance in young and middle-aged persons. Macular amyloidosis was the most common form and the most common site of involvement, the upper extremity and the inter-scapular/back region.J MEDICINE Jan 2018; 19 (1) : 35-39